2013
DOI: 10.4103/1305-7456.120687
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of elongated styloid process in Saudi population of Aseer region

Abstract: Objective:The study was performed to investigate the prevalence, morphology and calcification pattern of elongated styloid process in Saudi population of Aseer (Southern) region and its relation to gender and sub-age groups.Materials and Methods:This study was analyzed digital panoramic radiographs of 1,162 adults. Any radiograph with questionable styloid process was excluded from the study. The apparent length of the styloid process was measured by a single experienced dental and maxillofacial Radiologist. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
36
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 15 publications
11
36
2
4
Order By: Relevance
“…This finding was in accordance with Bozkir et al,19 Vadgaonkar et al,22 Roopashri et al23 and Shaik et al30 However, More and Aarani27 observed that the elongated styloid process was more common on the right side in their study population. Ilgüy et al6 and Custodio et al31 observed no difference in the length of the styloid process when the sides were compared.…”
Section: Discussionsupporting
confidence: 90%
“…This finding was in accordance with Bozkir et al,19 Vadgaonkar et al,22 Roopashri et al23 and Shaik et al30 However, More and Aarani27 observed that the elongated styloid process was more common on the right side in their study population. Ilgüy et al6 and Custodio et al31 observed no difference in the length of the styloid process when the sides were compared.…”
Section: Discussionsupporting
confidence: 90%
“…Most of the studies from different parts of the world have shown type 1 being the most common type of the styloid process, followed by type 2 and type 3 similar to our study [ Table 4]. [7,8,[10][11][12] Most of the studies have shown the type A as the most common pattern of calcification [7,10,11] [ Table 5]. In our study, type D was the most common pattern of calcification seen followed by type A.…”
Section: Discussionsupporting
confidence: 84%
“…[6] Therefore, it is necessary to define the type of elongation and calcification of each styloid in order to describe its radiographic appearance. [7] Awareness about the clinical and radiologic presentation of the styloid process elongation is important for all health practitioners involved in the diagnosis and treatment of head and neck pain. Eagle syndrome, sometimes called styloid or stylohyoid syndrome, is defined as the symptomatic elongation of the styloid process or mineralization of the stylohyoid ligament complex.…”
Section: Discussionmentioning
confidence: 99%
“…Putative normal length and prevalence values on previous studies are shown in Table 8. Prevalence of elongated SHC varies between 4.5% and 63.2% in studies which proposed 30 mm as normal length [5,13,18,22,28,30,35,37,40]. Andrei et al [1] determined the normal length of SHC as 35 mm and they reported the prevalence of elongated SHC as 40% in their CBCT study.…”
Section: Discussionmentioning
confidence: 99%